2013
DOI: 10.1177/1049732313481641
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Mothers’ Experiences

Abstract: We critically review qualitative research studies conducted from 2000 to 2012 exploring Western mothers' breastfeeding experiences. We used the search criteria "breastfeeding," "qualitative," and "experiences" to retrieve 74 qualitative research studies, which were reduced to 28 when the terms "existential'' and "research'' were applied. We found that the impact of technology and the pervasive worldwide marketing of infant formula devalued breastfeeding mothers' narratives in a number of ways. Women's bodies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
16
0
1
Order By: Relevance
“…2 Despite these figures, women are legally protected to breastfeed publicly (up to 26 weeks) by the Equality Act 2010 and any public service providers (eg, cafes, libraries, public transport, etc) have a legal obligation to protect breastfeeding women from discrimination. 3 Further qualitative research [4][5][6][7][8][9][10][11][12] highlights similar concerns to these reports, illustrating that a women's comfort to feed in public is related to the perceived social, cultural and public values around breastfeeding. It has been identified previously that such values may be derived from seeing very few women breastfeeding in public in the UK, 6 13 alongside a lack of breastfeeding support in TV, print and social media.…”
Section: Introductionmentioning
confidence: 78%
“…2 Despite these figures, women are legally protected to breastfeed publicly (up to 26 weeks) by the Equality Act 2010 and any public service providers (eg, cafes, libraries, public transport, etc) have a legal obligation to protect breastfeeding women from discrimination. 3 Further qualitative research [4][5][6][7][8][9][10][11][12] highlights similar concerns to these reports, illustrating that a women's comfort to feed in public is related to the perceived social, cultural and public values around breastfeeding. It has been identified previously that such values may be derived from seeing very few women breastfeeding in public in the UK, 6 13 alongside a lack of breastfeeding support in TV, print and social media.…”
Section: Introductionmentioning
confidence: 78%
“…In agreement with other studies, it was revealed that the secondary network is an important support for breastfeeding women, mainly when difficulties happen 6,7,9,18,20 . In this sense, the importance of care offered by health workers to women during the breastfeeding period is emphasized, as well as the recognition of their social networks, which makes it possible for them to feel treasured, aware of belonging, leading them to face the main problems of the breastfeeding phase and to avoid isolation and anonymity [7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Professional Counseling To Overcome Difficultiesmentioning
confidence: 99%
“…Some possible causes for early weaning that were mentioned were socioeconomic and geographical differences, which are barriers for women to receive quality health care and be monitored during the breastfeeding process 5 . In Brazil, starting in the 90s, some studies on breastfeeding demonstrated the importance of considering women capable of choices, of having certain sensibilities, histories, daily routines and as individuals who need somebody at their side for support and care [6][7][8][9] . In this perspective, it is necessary to consider both biological and social aspects of breastfeeding in order to understand the conditional factors of this practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research aimed to optimize breastfeeding promotion and support has greatly focused on the biomedical aspects of lactation, whereas the unique emotional breastfeeding experience has been poorly explored (7). Indeed, the breastfeeding process has been recognized as complex and challenging and mothers experience several emotions that shape their breastfeeding experience (8,9). Mothers are more likely to be satisfied with their breastfeeding experience by 12 months of infants' age when they have experienced positive emotions at 2 months postdelivery (10).…”
Section: Introductionmentioning
confidence: 99%